On Improving the Germination and Metabolism in Rice Seeds Using Priming with ZnO Nanoparticles - Shrivastava, Dr. Shilpi; Verma, Dr. Aloke (Migration Letters, 2023)
Rice, a crucial staple that supports a significant proportion of the world population, is at the forefront of efforts to meet the increasing need for food resulting from rapid population increase. However, the pursuit of achieving optimum rice production is fraught with complex obstacles that need the implementation of novel strategies. This work highlights the significance of examining the complexities of germination and metabolism in rice seeds since these crucial initial development processes have a lasting impact on crop productivity. Incongruous results and methodological constraints have characterized conventional research initiatives. To overcome these challenges, this research proposed Germination and Metabolism in Rice Seeds Analysis using ZnO Nanoparticles (GMRSA-ZNP). GMRSA-ZNP exploits the remarkable characteristics of ZnO nanoparticles to enhance seed vigor and metabolic functions. The empirical data obtained via rigorous numerical analysis provides clear evidence of the significant transformational capabilities of GMRSA-ZNP. These capabilities are evident in the considerable improvements seen in several aspects, including germination percentage (92.3%), starch metabolism (130.1 μg/g), starch breakdown rate (0.95 mg/g/h), nutrient absorption (32 mg/kg), and seedling vigor index (155.6). The data highlight the significant influence of GMRSA-ZNP in transforming the practice of rice production, leading to increased crop productivity and successfully meeting the urgent need for food worldwide.